Titanium-protoporphyrin IX coordinated nanoparticles for tumor photodynamic and sonodynamic combination therapy - Wei Wang; Yong Li; Yan Li; Yuzi Huang; Peng Geng; Liu Huang; Youfang Zhang; Wenquan Huang; Shuzhang Xiao (Biofunctional Materials)
Driven by advancements in nanotechnology and biomedicine, multifunctional nanomaterials integrating photodynamic therapy (PDT) and sonodynamic therapy (SDT) are paving new avenues for efficient tumor treatment. In this study, titanium-protoporphyrin coordinated nanoparticles (TiPPs) with a uniform particle size (~70 nm) were successfully fabricated via coordination self-assembly, achieved through the rational selection of a biocompatible metal and functionalized organic ligand. Experimental results demonstrated that after 6 minutes of light or ultrasound irradiation, TiPPs exhibited high reactive oxygen species (ROS) generation efficiency, with DPBF oxidation rates of 71.6% (light group) and 46.6% (ultrasound group), confirming their excellent photo- and sono-responsive ROS production capabilities. Notably, in vitro cytotoxicity assays and in vivo tumor-bearing mouse model studies revealed that the PDT-SDT combination therapy achieved significantly higher tumor inhibition rates than single-mode treatments. This study not only establishes an efficient dual-modal synergistic therapeutic platform but also introduces an innovative paradigm for the development of multifunctional sensitizers through metal-organic coordination engineering, highlighting promising clinical applications.